Systems Pharmacology-based Drug Discovery and Active Mechanism of Ganoderma lucidum Triterpenoids for Type 2 Diabetes Mellitus by Integrating Network Pharmacology and Molecular Docking - Shi, Junkai; Chen, Jialiang; Cheng, Chitong; Li, Wei; Li, Ming; Ye, Shuhong; Liu, Zhaofang; Ding, Yan (Current Pharmaceutical Design, 2025)
BackgroundType 2 Diabetes Mellitus (T2DM) is a chronic metabolic disease primarily characterized by insufficient insulin secretion or reduced insulin sensitivity in the body's cells, leading to persistently high blood glucose levels. Ganoderma lucidum triterpenoids, as important secondary metabolites of Ganoderma lucidum, have shown preliminary potential efficacy in the treatment of T2DM according to existing research. However, due to the structural complexity and diversity of these triterpenoid compounds, as well as the intricate interactions between their therapeutic targets and active ingredients, the precise molecular and pharmacological mechanisms remain to be further explored.ObjectiveIn the present research, we aim to fully employ the integrated approach of network pharmacology and molecular docking methodologies, delving deeply into the potential therapeutic targets and their underlying pharmacological mechanisms in the management of T2DM via Ganoderma lucidum triterpenoids.MethodsThe active compounds were sourced from prior research and the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Their potential targets were predicted with the aid of Swiss Target Prediction. Genes linked to T2DM were gathered from DisGeNET and GeneCards. Using Cytoscape, we established the network connecting active ingredients, targets, and pathways, and the target protein-protein interaction (PPI) network was created using data from the STRING database. The core targets of Ganoderma lucidum triterpenoids underwent gene enrichment analysis via DAVID. Lastly, to validate our chosen Ganoderma lucidum triterpenoids, we conducted molecular docking experiments between the compounds and their targets.ResultsA total of 53 Ganoderma lucidum triterpenoids and 116 associated targets were identified. Among these, SRC, MAPK1, MAPK3, HSP90AA1, TP53, PIK3CA, and AKT1 emerged as pivotal targets. We retrieved 447 Gene Ontology (GO) functional annotations and 153 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, notably including the PI3K-Akt signaling pathway, Endocrine resistance, Rap1 signaling pathway, and Lipid and Atherosclerosis, which are known to be associated with T2DM. Our findings suggest that Ganoderma lucidum triterpenoids may confer resistance to T2DM through mechanisms related to hyperexcitability, cell death, cell survival, proliferation, differentiation, and inflammation.ConclusionA comprehensive, interdisciplinary, and multi-technology approach has been established, which uncovers the collaborative effects and underlying principles of Ganoderma lucidum triterpenoids in the management and therapy of T2DM from a holistic perspective. This approach provides new insights into the development of novel biological control products for Type 2 Diabetes Mellitus (T2DM) and lays the foundation for future systematic studies on the interactions between Ganoderma triterpenes and different targets, elucidating their primary and secondary pathways for lowering blood glucose.
Keywords: Network pharmacology